Resurrecting Urban Heritage with Contemporary Adaption: The Reconstruction of the Porcelain Tower in Nanjing (China) - Pengfei Ma; Mengbi Li; Xiangning Li (Land, 2022)
This article explores how reconstruction design can be used in urban heritage as an adaptive approach to creating a continuous cultural dynamic for urban regeneration. The case that is studied is the rebuilding project of the Porcelain Tower of Nanjing, well-known to westerners as a splendour of the East. The research strategy stems from the epistemological paradigm of interpretivism and relies mainly on qualitative research methods. The ethic of refashioning a past legacy is discussed by reviewing the relevant theories and documents. It is argued that the rationale for rebuilding heritage should be judged on a case-by-case basis. From the perspective of urban cultural regeneration, rebuilding can be an appropriate solution to reviving heritage within the bounds of authenticity. Respecting the delicate balance between historical significance and contemporary sustainability, urban heritage can sometimes best be served by modern reconstruction. This paper, therefore, identifies the modern Porcelain Tower as an urban landmark that distinguishes Nanjing among Chinese cities and satisfies the cultural demand for sustainable local urban regeneration. Whilst the modern pagoda is not historically inaccurate, its reconstruction was determined without public engagement in a way that emphasises the government’s view of its history and value.